Network meta-analysis comparison of Hydrus, Istent microinvasive glaucoma surgery implants, and phacoemulsification for handling open-angle glaucoma - Anjaswari, Niska Ayu; Primitasari, Yulia; Wungu, Citrawati Dyah Kencono; Komaratih, Evelyn; Sasono, Wimbo; Sulistiawati, Sulistiawati (Edelweiss Applied Science and Technology, 2024)
This study aims to analyze the comparative effectiveness of two Microinvasive Glaucoma Surgery (MIGS) devices, Hydrus and iStent, in combination with phacoemulsification in patients with open-angle glaucoma. The protocol for this network meta-analysis registered in PROSPERO under registration number CRD42023404273. Literature search was conducted following PRISMA guidelines. RCTs were retrieved from multiple databases based on inclusion and exclusion criteria. Evaluated parameters included intraocular pressure, visual acuity, the number of postoperative anti-glaucoma medications, and complications. Mean probability for each treatment was obtained using SUCRA. Ten selected articles originating from America and Europe with varying follow-up periods. SUCRA analysis shows that the combination of Hydrus and phacoemulsification ranks highest in reducing IOP at 92.38%, compared to the combination of iStent and phacoemulsification at 56.99%, and phacoemulsification only at 0.62%. The best outcomes for post-intervention BCVA ≥ 20/40 are reported in the SUCRA diagram (63.88%), as well as for the best post-intervention medication use (85.5%) and minimal complications (86.41%), which were observed in combination of iStent and phacoemulsification. The Hydrus combination intervention showed the greatest reduction in IOP, while the iStent combination more effective in improving visual acuity and reducing postoperative anti-glaucoma medication use and had the fewest overall postoperative complications. This study highlights that MIGS interventions, particularly Hydrus and iStent combined with phacoemulsification, offer significant benefits and show more effective compared to standalone phacoemulsification.